Methodological aspects for modeling the environmental risk of transporting hazardous materials by road - Cordeiro, Francyelly Giovany [UNESP]; Bezerra, Barbara Stolte [UNESP]; Peixoto, Anna Silvia Palcheco [UNESP]; Ramos, Rui António Rodrigues [UNESP] (Elsevier, 2016)
The main objective of this paper is to establish the procedures necessary to the development of a model for the environmental risk assessment of accidents involving Transporting Hazardous Materials by Road (THMR). Quantifying the environmental risk is useful in identifying areas with a high risk of accidents, which can be later discarded as main routes; orienting efficient emergency response operations; and assessing policies aimed at reducing these risks. Taking this into consideration, this study endeavors to identify the methodological aspects make possible the assessment of the impacts that arise from accidents involving the transportation of hazardous materials by road and to implement such methodological aspects in a Geographic Information System (GIS).
Keywords: Environmental risk; Geographic information system; Hazardous goods; Multicriteria evaluation; Risk modeling